Malaria parasite cGMP-dependent protein kinase regulates blood stage merozoite secretory organelle discharge and egress. - Christine R Collins; Fiona Hackett; Malcolm Strath; Maria Penzo; Chrislaine Withers-Martinez; David A Baker; Michael J Blackman (PLoS Pathogens)
The malaria parasite replicates within an intraerythrocytic parasitophorous vacuole (PV). Eventually, in a tightly regulated process called egress, proteins of the PV and intracellular merozoite surface are modified by an essential parasite serine protease called PfSUB1, whilst the enclosing PV and erythrocyte membranes rupture, releasing merozoites to invade fresh erythrocytes. Inhibition of the Plasmodium falciparum cGMP-dependent protein kinase (PfPKG) prevents egress, but the underlying mechanism is unknown. Here we show that PfPKG activity is required for PfSUB1 discharge into the PV, as well as for release of distinct merozoite organelles called micronemes. Stimulation of PfPKG by inhibiting parasite phosphodiesterase activity induces premature PfSUB1 discharge and egress of developmentally immature, non-invasive parasites. Our findings identify the signalling pathway that regulates PfSUB1 function and egress, and raise the possibility of targeting PfPKG or parasite phosphodiesterases in therapeutic approaches to dysregulate critical protease-mediated steps in the parasite life cycle.